Character Marker and Kinship of Accession of Robusta Coffee (Coffea canephora) in Jember Based on Morphological Characters - Afifah, Dwi Nur; Indah, Novita Kartika (LenteraBio : Berkala Ilmiah Biologi, 2023)
Jember Regency is the area with the highest coffee productivity in East Java. Coffee is an export commodity that is taken into account in strengthening the country’s foreign exchange. Robusta coffee is one of the coffee varieties that undergoes cross-pollination so that coffee with new characters appears as a result of this cross-breeding. These new characters are hard to tell apart. Therefore, this study aims to determine character markers and analyze kinship relationships based on the morphological characters of 19 Robusta coffee cultivars in Jember, making it easier to distinguish, describe, and identify. This research is descriptive research both qualitatively and quantitatively. The research procedure includes three stages, namely exploration and collection as well as documentation, observation and measurement, as well as character markers and analyzing kinship relationships. Exploration was carried out in the Districts of Silo, Jenggawah, Ledokombo, Arjasa, and Panti to obtain 19 Robusta coffee cultivars. The observed morphological characters were 15 quantitative characters and 15 qualitative characters. The thirty characters were used by Principal Component Analysis (PCA) to determine the marker characters of 19 Robusta coffee cultivars and determine their kinship in the form of a phenogram. The results of the analysis showed diagnostic characters, including: stipule shape, leaf shape, leaf tip shape, fruit color, fruit shape, fruit disk shape, pulp thickness, HS seed thickness, HS seed color, HS seed shape. The results of PAST4 analysis of Robusta coffee cultivars were divided into 4 groups based on morphological characters and by phenogram divided into two main groups.